Molecular and phenotypic characterization of endophytic Sebacinoid strains - Basiewicz, Magdalena; Justus Liebig University Giessen (My University, 2010)
The order Sebacinales belongs to a taxonomically, ecologically, and physiologically diverse group of fungi within the Phylum Basidiomycota. Using several molecular techniques they were detected all over the world. Few isolates, classified into the clade B, are available at the moment: the root colonizing mutualistic fungus Piriformospora indica, various Sebacina vermifera isolates from autotrophic orchids, as well as Piriformospora glomeralium (ex multinucleate rhizoctonia DAR29830, Warcup). All of them were described as growth promoting and resistance inducing fungi. In the present work, seven Sebacinales isolates of the clade B were characterized molecularly and phenotypically. In addition, the presence in Germany of fungi closely related to P. indica was proven.Phylogenetic analyses conducted using DNA sequences from the 28S and the translation elongation factor 1 & #945; gene (TEF) showed that analyzed Sebacinales isolates represent at least 3 distinct groups of isolates. Further, three independent environmental samples, collected from two different areas in Germany were examined. The analysis demonstrated that the sample respresented organisms closely related to P. indica. The analyzed introns of their TEF gene had the same sequence. This finding suggests that one genotype is present in different area of Germany which is associated with roots of taxonomically diverse plants, including Anthyllis, Medicago and Lolium. Moreover, the fungal genome sizes of five sebacinoid isolates were estimated using Pulsed Field Gel Electrophoresis (PFGE) and real time PCR based on the absolute quantification of a single copy gene (TEF). The fungi have at least 4 to 7 chromosomes and a genome size ranging from 21 to 26 Mb.Morphological, physiological and molecular studies of the multinucleate rhizoctonia DAR29830 isolate proved that this strain is the closest related to P. indica, the most investigated member of the Sebacinales. Therefore it is designed in this study as a provisional new species named Piriformospora glomeralium sp. nov.Seven Sebacinales strains were tested for extracellular enzyme production including peroxidase, laccase, protease, pectinase, and cellulase. In general, the enzymatic test demonstrated strong protease activity in cultures of all the analyzed fungi. The orchid mycorrhiza isolates showed stark laccase activity and lack of cellulase production in axenic culture whereas the Piriformospora strains were able to digest this plant cell wall component. Only one isolate proved to secrete pectinase. All Sebacinales isolates except P. indica and P. glomeralium that were co cultured with a fungal competitor (Rhizoctonia solani) generated significant amounts of laccase. The presence of a plant host, life or dead, had noticeable impact on laccase secretion by P. indica but no influence on P. glomeralium enzyme exudation. In addition, production of laccase, peroxidase, esterase, and lipase by P. indica in response to plant host was spectrophotometrically investigated. Diversity in laccase and lipase activity was observed mostly in presence of decay plant material. Differences in the enzyme profile for the analyzed Sebacinales strains agreed mostly with their phylogenetic position. In addition, genome estimation as well as karyotype analysis clearly confirmed the phylogenetic study and proved that Sebacina vermifera should be considered as complex of isolates. Moreover, laccase secretion by P. indica can be induced only by the presence of the plant symbiotic partner.

Die Ordnung der Sebacinales gehört zu einer taxonomisch, ökologisch und physiologisch diversen Gruppe von Pilzen im Phylum der Basidiomyceten. Weltweit können sie durch verschiedene molekulare Techniken detektiert werden. Wenige Isolate, klassifiziert im Untergruppe B, sind zurzeit verfügbar: der Wurzel kolonisierende, mutualistische Pilz Piriformospora indica, verschiedene Sebacina vermifera Isolate von autotrophen Orchideen, genauso wie Piriformospora glomeralium (ex multinucleate rhizoctonia DAR29830, Warcup). Für alle wurde beschrieben, dass sie das Wachstum fördern und Resistenz vermitteln gegen biotischen und abiotischen Stress. In der vorliegenden Arbeit wurden sieben Sebacinales Isolate der Untergruppe B molekularbiologisch und phänotypisch charakterisiert. Zusätzlich wurde das Vorkommen eines zu P. indica nahe verwandten Genotyps in Deutschland bewiesen. Phylogenetische Analysen, unter Verwendung von DNA Sequenzen aus 28S und dem Translationselongationsfaktor 1 & #945; Gen (TEF), zeigten, dass diese Organismen mindestens drei verschiedene Isolat Gruppen repräsentieren. Zudem wurden drei unabhängige Proben aus zwei verschiedenen Orten Deutschlands untersucht. Die Analyse zeigte, dass sie eng verwandt sind mit P. indica. Die analysierten Introns des TEF Gens haben die gleiche Sequenz. Dies impliziert, dass ein Genotyp, welcher in verschiedenen Gegenden Deutschland vorkommt, mit den Wurzeln taxonomisch diverser Pflanzen, inklusive Anthyllis, Medicago und Lolium, assoziiert ist.Darüber hinaus wurde die Genomgröße von fünf Sebacinoid Isolaten durch Pulsed Field Gel Electrophorese (PFGE) und quantitative Real time PCR bestimmt. Die Pilze besitzen zwischen vier und sieben Chromosomen und die Genomgröße variiert von 21 bis 26 Mb. Morphologische, physiologische und molekulare Untersuchungen des multinuklearen Rhizoctonia Isolates zeigten, dass dieser Stamm am engsten mit P. indica verwandt ist und daher in dieser Abhandlung als Piriformospora glomeralium sp. nov. benannt wird.Sieben Sebacinales Stämme wurden auf extrazelluläre Ezymproduktion von Peroxidase, Laccase, Protease, Pectinase und Zellulase getestet. Generell zeigten diese Tests eine starke Peroxidase Aktivität der Kulturen bei allen analysierten Pilzen. Die Orchideen Mycorrhiza Isolate zeigten eine starke Laccase Aktivität und ein Fehlen von Zellulase Produktion in axenischen Kulturen während die Piriformospora Stämme diese Zellwandkomponente zersetzen konnten. Nur ein Isolat sekretierte Pectinase. Alle Sebacinales Isolate außer P. indica und P. glomeralium co kultivert mit einem pilzlichen Konkurrenten (Rhizoctonia solani) bildeten signifikante Mengen an Laccase. Die Gegenwart des Wirts, tot oder lebendig, hatte einen bemerkenswerten Einfluss auf die Laccase Produktion von P. indica und keinen Einfluss auf die Enzymexudation von P. glomeralium. Zusätzlich wurde die Produktion von Laccase, Peroxidase, Esterase und Lipase bei P. indica in Bezug auf den Wirt photospektrometrisch untersucht. Unterschiede in Laccase und Lipase Aktivität wurden vor allem in Gegenwart von totem Pflanzenmaterial beobachtet. Unterschiede in den Enzymprofilen der analysierten Sebacinales Stämme korrelieren mit ihrer phylogenetischen Position. Außerdem bestätigen die Genomgrößenbestimmung und die Karyotypen Analyse, dass Sebacina vermifera als ein Komplex von Isolaten angesehen werden sollte. Zudem kann die Laccase Sekretion bei P. indica nur durch Anwesenheit eines symbiotischen Partners induziert werden.
Keywords: Sebacinales; Piriformospora indica; Pilz-Genomgröße; extrazelluläre Ezymproduktion; Sebacinales; Piriformospora indica; genome size estimation; extracellular enzyme production; ddc:570